FEMINIZAÇÃO DO TRABALHO NO CONTEXTO DA REESTRUTURAÇÃO PRODUTIVA NA SAÚDE PÚBLICA: rebatimentos no Serviço Social e na Medicina no HUUFMA - Dias, Marly de Jesus Sá (2008)
It is analysed the feminization process in the public health space work, in the context of Social Service and Medicine of the Hospital Universitário da Universidade Federal do Maranhão, characterized by the majoritary constitution of women, chiefly from the productive reestructuration, in wich the big capital gets spread with adoption of flexible measures that refute the paper of State, in the politics of health and profissions, some of them strongly tokened by a gender divide, as the exemple of the Social Service and the Medicine. It is perceived, based on the fundaments of the sexual division of work, the specificities that translate the increase of female activity rate in present, as well as the inequalities that it expresses in terms of insertions, occupations and remunerations, letting foresee the currency of the patriarchy-racismcapitalism domination system. It is concluded with an analyses of the functionality of the feminization of work in capitalism production, looking to establish a relation with the thinking of this reaserch's subjects, in order to identify the advances and the challenges that the actual female progression endures.